Refinement of a Fertiliser-producing Urinal - Mufunde, Tariromunashe (Department of Civil Engineering, 2022)
Wastewater recovery plays a crucial role in meeting sustainable and environmental challenges. Eco-friendly, nutrient recycling is a more sustainable and environmentally friendly method of waste recovery because it reclaims vital components from waste streams and utilises their potential as valuable resources. Effective wastewater treatment of human excreta retrieves nutrients that can make an essential contribution to fertiliser manufacturing, and thus to agriculture and food sustainability. Waste streams essentially become resources. This research investigated ways in which a novel fertiliser-producing urinal makes this possible. The most nutrient-rich portion of domestic wastewater is human urine. Urine contains the three nutrients that are essential for commercial fertilisers: nitrogen (N), phosphorus (P), and potassium (K). Commercially available P fertilisers contain rock phosphate, calcium orthophosphates, ammonium phosphates, ammonium polyphosphate and nitric phosphate but the production of these fertilisers is energy-intensive and not sustainable. In a sustainable eco-cycle, recovering valuable nutrients from urine allows for these nutrients to be recycled to the agriculture sector, thus reducing environmental pollution. Appropriately managed, wastewater recovery from design-specific urinals will also produce a financial reward because the recovered fertiliser can be sold. Although urine only makes up around 1% of the total domestic wastewater volume, when recovered, it offers significant value as a nutrient resource. Several technologies, such as urine diversion sanitation systems and waterless urinals, can be used to capture the nutrients identified above (N, P, and K) by separating concentrated urine at the point of collection. Waterless urinals are not as commonly used as they could be because urine salt precipitation can cause pipe clogging leading to maintenance problems. This research aimed to improve on one promising technology: a novel, waterless fertiliser-producing urinal that collects and treats nutrients on-site for subsequent recovery at resource recovery plants, either on-site or in larger decentralised plants. This urinal system is not connected to the sewer network and hence the pipe clogging concerns are avoided. The original, novel, fertiliser-producing urinal adapted for improvement in this research was made from plastic components: a 25 L container, urine collection funnel and a backsplash board to prevent urine from spraying back out of the funnel. The collection tank was pre-dosed with calcium hydroxide powder (10 g Ca(OH)2/L of urine). Once the pre-dosed calcium hydroxide came into contact with the urine, calcium phosphate precipitated. The resulting urinal contents were a mixed precipitate consisting of calcium hydroxide, calcium phosphate and magnesium hydroxide. Pre-dosing with calcium hydroxide maintained high pH values (above 11). These were required to inhibit enzymatic urea hydrolysis, thus preventing irreversible loss of nitrogen (as ammonia gas), an essential element of fertiliser production. The lack of mixing of the contents of this original urinal design would potentially result in a pH gradient, in which localised sections of the urinal would have pH levels below the enzymatic urea hydrolysis threshold (pH 11). Manual mixing was done once a day for 30 seconds by swirling the collection container. The design was adequate and completed the task of collecting urine using a single urinal in a university restroom but, as the volume of the urinal increased, manually mixing with the swirling method became laborious. Manual mixing (swirling) was therefore determined to be neither practical nor ideal when dealing with multiple fertiliser-producing urinals in a commercial building or any other public space. The research opportunity became clear – the urinal needed to include a mixing mechanism. The focus of this study was therefore to improve on the existing urinal by redesigning it to accommodate mixing within the system. Four urinal designs were considered: three with mechanical manual mixing and one with electrical mixing. These progressive designs improved on the original design. The primary refined urinal design used in this study included a 20 L collection tank with a funnel and a foot pedal with a link to the container, allowing the urinal contents to be mixed manually using a mechanical mechanism. The manual mixing urinals used circular discs, whereas the electric mixing urinal used an electric stirrer. In both design types, the urinal contents were mixed by stepping on the foot pedal while urinating. The mechanical manual system mixed for the duration of urination, while the electric mixing system mixed for 15 seconds. The pH recorded in the urinal system at a given time was used to determine mixing efficiency. Considering previous studies, a pH less than 11 indicated the possibility of enzymatic urea hydrolysis, while a pH greater than 11 indicated the possibility that enzymatic urea hydrolysis had not occurred. As a result, the pH of urinal contents was used as a proxy for the presence of enzymatic urea hydrolysis in this study. The third manual mixing design and the fourth electric mixing design successfully mixed and inhibited enzymatic urea hydrolysis. These two designs could both be implemented for the urinal system; however, the manual mixing design was determined to be more sustainable as it does not require any electrical power. The fertiliser produced from the collected urine could be recovered in two forms: solid (rich in calcium phosphate) and liquid (rich in urea and potassium). Because insufficient mixing in the system led to potentially localised pH gradient, a portion of this study focused on analysing the calcium phosphate (solid fertiliser) produced from the urinal contents at different pH values. Particles with needle-like shapes formed at a constant temperature of 21ºC and continuous stirring at 500 rpm. Phosphate compounds formed at low pH, hydroxyapatite formed across the pH range (7 to 12) and calcite formed at high pH values. Settling experiments were then carried out to determine how quickly the fertiliser sludge settled in three different mediums: water, stabilised real human urine and synthetic human urine. The settling velocity determines how long it takes for the urinal contents to settle in the urinal. As a result, the settling velocity would determine the frequency of mixing required in the urinal to inhibit enzymatic urea hydrolysis - a faster settling velocity would mean mixing frequency has to be high. The experimental results revealed that water had a settled sludge volume of 48% in the first two minutes, synthetic urine had a volume of 28% and stabilized urine had a volume of 22%. Stokes' Law was used to calculate the theoretical settling velocity, which was then compared to the experimental velocity. The Stokes' Law results showed a significantly high settling velocity of 1.22 cm/s on average. According to the urinal testing experiments, an hour without mixing was sufficient to keep the urinal contents above the enzymatic urea hydrolysis pH threshold of 11. Due to differences in densities, the actual fertiliser sludge would take longer to settle than the synthetic urine sludge. An economic analysis of the urinal operational system was also performed for a typical 1000-person commercial building (assuming urine was only collected from 500 men) to determine the feasibility of an external service provider (Urine Recovery company) installing and managing all associated operations of the urinal system investigated and refined in this study. This analysis considered capital costs, operating costs, indirect benefits, revenue, and profits. Net present value was also considered to measure viability of operating the system. The given scenario would see the Urine Recovery company collecting and treating the urine to recover fertiliser on-site (at the commercial building premises). The manual mechanical mixing urinal design was considered for urine collection. The treatment would follow the sequence of alkaline stabilisation (using Ca(OH)2), solid/liquid filtration and reverse osmosis (RO) for volume reduction. This scenario yielded revenue of ZAR1.25 million per year from fertiliser sales and an annual urinal system service fee of ZAR1 500/urinal charged to the commercial building based on 89.7 kL of urine/year collected from 20 urinals. A solid and liquid fertiliser would be produced, the fertiliser would be sold as three streams – solid (at ZAR18.50/kg), 41% of the niche liquid sold to nurseries (at ZAR153/L) and the remaining 59% sold as bulk liquid fertiliser (at ZAR 9.56/L). Indirect benefits of R32 000 per year are expected for the commercial building as a result of water savings, and an additional ZAR2 300 for the Urine Recovery company from recovered water permeate through the RO system. A net present value of ZAR1.8 million was calculated over a five-year investment period. The capital cost of ZAR77 900 was calculated which included the production of urinals and the RO unit (1.72 m3 /day). The urinal production (estimated at R5 590 per urinal) is expected to reduce over time considering economies of scale. In conclusion, this study demonstrated how the novel, fertiliser-producing urinal can aid in nutrient recovery by producing fertiliser through a mixing mechanism that inhibits enzymatic urea hydrolysis. The design was deemed adequate and completed the task of collecting urine in a restroom so that calcium phosphate (solid fertiliser) formed in the removable urinal collection container. The design only considered urine collected from men, but the fertiliser yields could increase substantially if unisex urinals or female-only urinals were also installed. The designed urinal system is characterised by its simplicity, easy installation, and maintenance. Literature has concentrated on using feet instead of hands to open taps both as a water-supply solution and as a method to combat infection. Hence, the use of foot pedals in sanitation process is not novel, but this is the first time it has been used to operate a urinal. Recovery of valuable resources from the urinal designed and refined in this study can contribute to a sustainable and circular sanitation economy.